SAT0575 Association of human leukocyte a, b and dr antigens in patients with chikungunya virus infection. (15th June 2017) - Rueda, JC; Angarita, J-I; Santos, AM; Saldarriaga, E-L; Pelaez-Ballestas, I; Zaldivar-Castaño, B; Londono, J
Abstract : Background: Host factors like innate and adaptive immune response play an important part in disease susceptibility. Also, the role of host genetics factors in the pathogenesis of viral diseases have been reported. Human leukocyte antigen (HLA) is responsible for initiating innate and adaptive immune responses. Studies have demonstrated HLA class II alleles association to susceptibility or resistance to chikungunya virus infection (CHIKV), however there is no evidence of association studies of HLA class I and II in the Latin-American CHIKV epidemic. Objectives: To evaluate the association of human leukocyte A, B and DR antigens in a group of Colombian patients with CHIKV. Methods: Characterization of HLA allele A, B, and DR of 62 patients with confirmed CHIKV was compared with 100 unrelated healthy subjects as a control group. The comparison between the different allele frequencies in the patient group and the control population was performed using chi 2, with Bonferroni correction. A p value <0.05 was considered to be significant. The magnitude of associations was assessed using odds ratio (OR) and confidence intervals (CI) of 95%. To establish the homogeneity of the studied groups, the Hardy-Weinberg disequilibrium was used. Results: Of the 62 patients studied 46 were female (74, 2%). The mean age was 45, 0 (SD±16, 8) years. Most of the patients were from Barranquilla (64, 5%; n: 40). Mean CHIKV immunoglobulin G (IgG) was 38, 6 SU (SD±21, 7), while IgM was 13, 3 SU (SD±7, 6). Also C reactive protein levels were high (mean: 14, 7 mg/L; SD±8, 4). Association alleles of HLA-A, and DR are depicted in table 1 . No association was found with HLA-B alleles. Conclusions: Our study demonstrated the alleles A*28 and A*29 to be associated with resistance to CHIKV, and alleles A*68, DRB1*01, DRB1*04 and DRB1*13 to be associated with susceptibility to CHIKV. No association was found in any HLA-B alleles. Disclosure of Interest: None declared